Adapting international experience to the Deposit Guarantee System in Ukraine - Alyeksyeyev, Ihor; Mazur, Andriana (Adaptacja międzynarodowego doświadczenia do systemu gwarantowania wkładów na Ukrainie, 2018)
The research objective of the article is the substantiation of methodological and applied recommendations for improving deposit guarantee system in Ukraine in view of the international experience. The study object is the deposit guarantee system management in the framework of reforming the Ukrainian legislation aimed at establishing a mechanism of deposits guaranteeing. During the research there were used such methods as: dialectical method and methods of analysis and synthesis – to study the features of deposit guarantee systems of developed countries, the characteristics of mechanism for returning deposits and international law peculiarities; statistical method – to analyze the indicators of banking system in Ukraine and credit unions (CU), for empirical determining CU to banks indicator ratio as well; structural and logical analysis – to develop theoretical and methodological principles of forming effective deposits guaranteeing mechanism in Ukraine. The need to ensure the system of deposits guaranteeing not only to individuals but also to individual-private entrepreneurs and legal entities was established. This will facilitate the development of small and medium businesses in the country. There were analyzed peculiarities of credit unions activity in Ukraine in the context of reforming the banking system. The possibility of including the credit unions to the deposit guarantee system of Ukraine by the example of the EU countries and the world was substantiated. There were characterized necessary amendments to the national legislation in the field of deposit guaranteeing and the effective mechanisms for their implementation were proposed
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 2, s. 9-21
Keywords: Deposit Guarantee System; Deposit Guarantee Fund; household deposit; deposit ensuring; credit unions (CU); system gwarantowania wkładów; fundusz gwarantowania wkładów; wkłady osób fizycznych; gwarantowanie wkładów; unie kredytowe (UK)